2021
DOI: 10.1126/sciadv.abh2399
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin targets a common molecular mechanism for cognitive impairment and increased craving in alcoholism

Abstract: Alcohol-induced mGluR2 deficits are restored by psilocybin, resulting in a rescue of pathological behaviors in alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 82 publications
3
63
0
Order By: Relevance
“…Only sub-chronic treatment with psilocybin produced a short-lasting anti-relapse effect (220). A recent study showed that psilocybin restored alcohol dependence-induced metabotropic glutamate receptor (mGluR2) down-regulation and reduced alcohol-seeking behavior in rats (221). Interestingly, in a rodent food reward model, low dose psilocybin and ketamine failed to positively affect motivation or attention, though subtle improvements in attention and impulsive behavior were noted in "low performing" rats (222).…”
Section: Addictionmentioning
confidence: 99%
“…Only sub-chronic treatment with psilocybin produced a short-lasting anti-relapse effect (220). A recent study showed that psilocybin restored alcohol dependence-induced metabotropic glutamate receptor (mGluR2) down-regulation and reduced alcohol-seeking behavior in rats (221). Interestingly, in a rodent food reward model, low dose psilocybin and ketamine failed to positively affect motivation or attention, though subtle improvements in attention and impulsive behavior were noted in "low performing" rats (222).…”
Section: Addictionmentioning
confidence: 99%
“…The psychedelic is, therefore, able to activate 5HT receptors as mentioned, ultimately leading to their downregulation [4]. In such instances, there is a compensatory upregulation in the metabotropic glutamate receptors (mGluR2/3) due to the inverse relationship between mGluR2/3 and 5HT-2A receptors [5]. The stimulation of 5HT-2A receptors on pyramidal cells in levels V and VI in the cortex by psilocin, a metabolite, leads to the release of glutamate in the prefrontal cortex [6].…”
Section: Review Mechanism Of Actionmentioning
confidence: 98%
“…A group of compounds that have recently sparked interest for their treatment potential is psychedelic drugs including psilocybin, dimethyltryptamine (DMT), mescaline, and lysergic acid diethylamide (LSD), among others [4]. These drugs are currently controversial for their hallucinogenic effects and recreational use; however, their resemblance to tryptophan enables them to act as serotonin agonists and activate 5HT receptors, mainly the 5HT-2A receptor [5]. This effect makes them promising candidates in the treatment of substance abuse disorders as well as mood disorders [6].…”
Section: Review Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…G*Power analysis (two-tailed unpaired t test; α = 0.05; power = 0.80) conducted in previous CIE rats (Hirth et al, 2016;Meinhardt et al, 2021;Sommer et al, 2008;Uhrig et al, 2017) suggested a total of 16 rats (N = 8/group) with an effect size of Cohen's d = 1.5.…”
Section: Induction Of Alcohol Dependencementioning
confidence: 99%